Trends of Public Opinion among the Students of Jordanian Universities towards the Performance of Local Councils Al al- Bayt University students as a model - Bani Hassan, Amer Nasir Aqil Mashaqbeh (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to identify the trends of public opinion among Jordanian university students towards the performance of local councils: A case study: Al- Bayt University and to achieve the objectives of the study the questionnaire was developed for the purpose of data collection, distributed to (100) students of Al- Bayt University, and the SPSS program was used to find value Arithmetic averages, standard deviations, the Pearson correlation coefficient and the t- test, and results of this study appear that there is a statistically significant relationship between public opinion trends and the performance dimensions of local councils, demonstrating the enhanced ability of individuals to perform local councils through cooperation build relationships among students and increase their cohesion. The study also recommended that more scientific studies should be conducted on the trends of public opinion towards the performance of local councils.